On the Economics of Regional Powers: Comparing China, India, Brazil, and South Africa - Robert Kappel (German Institute of Global and Area Studies (GIGA), 2010)
As the conception of and debates on regional powers have been led by political science, this pa-per aims to contribute to the discussion from an economics perspective. Based on the discussion of different concepts of economic power - such as those of Schumpeter, Perroux, Predöhl, or Kindleberger - concepts of technological leadership, and the global value chain approaches, the paper develops a research framework for the economics of regional powers. This framework is then tested using descriptive statistics as well as regressions analysis, with a focus on the four regional powers Brazil, China, India, and South Africa. As economic power is relational, the re-lationship of regional powers to other nations in the region is analyzed. According to the findings, only limited statements on the economics of regional powers are possible: a regional power can be described as an economy with a relatively large population and land area which plays a dominant role in trade within the region and in the regional governance. The regional power develops its technological capacities, and its businesses act regionally and globally with increasing strength. – – Während Konzeption und Debatte über regional powers maßgeblich von politikwissenschaftlicher Forschung geprägt sind, leistet das Working Paper einen Beitrag zur Theorie der regional powers aus wirtschaftswissenschaftlicher Perspektive. Ausgehend von der Diskussion unterschiedlicher Konzepte wirtschaftlicher Macht (beispielsweise von Schumpeter, Perroux, Predöhl und Kindleberger), Konzepten zu technologischer Führerschaft und der Forschung über globale Wertschöpfungsketten wird ein Forschungsrahmen für die wirtschaftswissenschaftliche Analyse der regional powers entwickelt, der im Folgenden durch beschreibende Statistik und Regressionsanalyse an den Beispielländern Brasilien, China, Indien und Südafrika getestet wird. Da wirtschaftliche Macht ein relationales Konzept ist, wird die Beziehung der regional powers zu anderen Ländern der jeweiligen Region untersucht. Anhand der Ergebnisse sind begrenzte Aussagen über die Ökonomie der regional powers möglich: Eine regional power kann demnach als eine Volkswirtschaft mit verhältnismäßig großer Bevölkerung und Landfläche beschrieben werden, die eine dominante Rolle im Handel der Region und der regionalen governance-Struktur einnimmt. Die regional power entwickelt ihre technologi-schen Fähigkeiten weiter und ihre Unternehmungen agieren mit zunehmender Stärke sowohl auf regionalem als auch auf globalem Niveau.
Keywords: A12; B1; B29; C01; F14; F15; F23; F59; 330; Brazil; China; economic geography; economic leadership; economic power; growth; India; investment; public goods; regional powers; regression analysis; South Africa; technological change; value chain; trade